2014
DOI: 10.3892/mmr.2014.2823
|View full text |Cite
|
Sign up to set email alerts
|

Biological effect of ketamine in urothelial cell lines and global gene expression analysis in the bladders of ketamine-injected mice

Abstract: Ketamine is used clinically for anesthesia but is also abused as a recreational drug. Previously, it has been established that ketamine-induced bladder interstitial cystitis is a common syndrome in ketamine-abusing individuals. As the mechanisms underlying ketamine-induced cystitis have yet to be revealed, the present study investigated the effect of ketamine on human urothelial cell lines and utilized a ketamine-injected mouse model to identify ketamine-induced changes in gene expression in mice bladders. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…In our study, the dose of 30 mg·kg Ϫ1 ·day Ϫ1 has been previously shown to induce mouse ketamine cystitis (24). This dose did induce voiding dysfunction, as shown in this and another study (22), yet a higher ketamine concentration and/or longer exposure time might be needed to induce more severe lower urinary tract damage, like hematuria and hydronephrosis, in mice. It has been reported in a rat model that 50 mg·kg Ϫ1 ·day Ϫ1 ketamine injection induced hematuria at a 16-wk time point (8).…”
Section: Ketamine D Ketaminesupporting
confidence: 72%
See 2 more Smart Citations
“…In our study, the dose of 30 mg·kg Ϫ1 ·day Ϫ1 has been previously shown to induce mouse ketamine cystitis (24). This dose did induce voiding dysfunction, as shown in this and another study (22), yet a higher ketamine concentration and/or longer exposure time might be needed to induce more severe lower urinary tract damage, like hematuria and hydronephrosis, in mice. It has been reported in a rat model that 50 mg·kg Ϫ1 ·day Ϫ1 ketamine injection induced hematuria at a 16-wk time point (8).…”
Section: Ketamine D Ketaminesupporting
confidence: 72%
“…Recent reports have indicated that ketamine-treated rats exhibit increased expression of occludin and decreased expression of cadherin and the tight junction protein zonula occludens (ZO)-1, suggesting a defect in the urothelial barrier (8,18). Changes in keratin family genes were also observed in urothelia of ketamine-treated mice (22). Moreover, inflammatory molecules such as cyclooxygenase-2 and apoptotic signals were observed in urothelia, confirming the urothelial pathology in ketamine cystitis (10,17).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In fact, some authors have found in animal models evidence of increased permeability of the urothelium exposed to ketamine and this could explain the damage beyond the superficial layer. [13][14][15] As previously mentioned, the presence of apoptotic-like bodies in the monolayer experiments led us to suppose that apoptosis may play a role in the observed growth decline. The presence of apoptosis within the urothelium in patients with KIC has already been observed.…”
Section: Discussionmentioning
confidence: 61%
“…Baker et al showed that ketamine‐induced toxicity to urothelial cells by high and sustained intracellular calcium ion concentration, which ultimately led to apoptosis 40 . This damage acts in a dose and time‐dependent manner, stimulating mitochondrial‐dependent and endoplasmic reticulum stress apoptosis and autophagy 41,43‐46 . Chuang et al showed that ketamine and norketamine levels were much higher in the 28‐day treated group compared to the 14‐day group.…”
Section: Evidencementioning
confidence: 99%